Examining anxiety and stress regarding virtual learning in colleges of health sciences: A cross-sectional study in the era of the COVID-19 pandemic in Saudi Arabia - Tahani Alshammari; Sarah Alseraye; Rawabi Alqasim; Aleksandra Rogowska; Nouf Alrasheed; Musaad Alshammari (Elsevier, 2022)
Background: Stress and anxiety are relatively common, particularly in females and college students. Stress can impact students' overall performance and their physical and mental health. The COVID-19 pandemic has affected all aspects of life and is associated with high levels of psychological distress. It has considerably affected the education sector, not only locally but worldwide, forcing a shift in the education system from on-site to virtual learning. This cross-sectional study was undertaken to evaluate the prevalence of anxiety and stress regarding virtual learning among health sciences college students in the Kingdom of Saudi Arabia (KSA) after introducing blended virtual classes and exams and in-person laboratory training. The study was carried six months after the COVID-19 outbreak. Methodology: Participants were recruited by convenient sampling and snowballing strategies. Our study was conducted between November 18 and December 6, 2020. Questionnaires were employed; they included the General Anxiety Disorder-7 (GAD-7) scale and focused on the participants' attitudes toward virtual learning. The present research was validated by a pilot study, followed by implementing some amendments. Results: A total of 418 health sciences college students, aged 18-27 (M = 20.88, SD = 1.97), participated in the study. Our analysis indicated that more than half the sample (51.44%) reported a risk of moderate to severe GAD. Anxiety was recognized more frequently in women (72.09%) than in men (27.91%). Interestingly, our Χ2 analysis revealed an association between marital status and anxiety, with a higher risk of GAD found in single people (compared with married). In addition, we found that the risk of anxiety increased in junior students (1st-3rd year) compared to senior students (4th-6th year). Conclusion: Our study highlights the need to establish gender-based tailored mental health support systems that provide preventive measures. The study findings also recommend that institutions develop programs and platforms that safely support students to interact and seek guidance, particularly those at higher risk of stress, such as females and first-year students. Overall, our study underlines the need to pursue an understanding of the complicated nature of anxiety disorders..